1995
DOI: 10.1200/jco.1995.13.11.2764
|View full text |Cite
|
Sign up to set email alerts
|

Combined intraoperative radiation and perioperative chemotherapy for unresectable cancers of the pancreas.

Abstract: The patients who undergo IORT with electrons and treated with perioperative chemotherapy (5-FU leucovorin) followed by additional external-beam radiation and chemotherapy appear to have improved survival, with few early or late complications. Dose escalation of external-beam radiation and chemotherapy may further improve local control of disease and survival of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 17 publications
1
32
0
5
Order By: Relevance
“…9 -15 In initial studies, the MST for this treatment was reported to be approximately 15 months and the findings suggested that IORT enhanced survival in patients with locally advanced pancreatic carcinoma. 9,10 In addition, Mohiuddin et al 13 reported that the MST and 2-year survival rate of combined IORT and perioperative 5-FU chemotherapy were 16 months and 20%, respectively, and that this treatment improved survival. Nishimura et al 14 reported that a combination of IORT and EBRT produced better survival rates than EBRT alone when used to treat patients with unresectable pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…9 -15 In initial studies, the MST for this treatment was reported to be approximately 15 months and the findings suggested that IORT enhanced survival in patients with locally advanced pancreatic carcinoma. 9,10 In addition, Mohiuddin et al 13 reported that the MST and 2-year survival rate of combined IORT and perioperative 5-FU chemotherapy were 16 months and 20%, respectively, and that this treatment improved survival. Nishimura et al 14 reported that a combination of IORT and EBRT produced better survival rates than EBRT alone when used to treat patients with unresectable pancreatic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of biochemical modulation of 5-FU with LV has not been found successful in patients with metastatic carcinoma of the pancreas (Bruckner et al, 1988;De Caprio et al, 1989;Crown et al, 1991;Weinermann et al, 1994), however, its potential efficacy might have been obscured by the bulk of tumour burden in these patients. Three recently published trials using radiochemotherapy with 5-FU/LV in locally advanced pancreatic tumours, in fact, have demonstrated encouraging results with prolonged survival (Moertel et al, 1994;Mohiuddin et al, 1995;Prott et al, 1997). The use of cisplatin in the regimen was based on preclinical evidence that CDDP is a potent radiosensitizer and on its successful addition to 5-FU ± radiation in the treatment of pancreatic and other malignancies, including squamous cell carcinoma of the head and neck, oesophageal and anal carcinoma (Rothman et al, 1991;Nicolson et al, 1995;Hörmann, 1996;Popescu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Intraoperative radiation therapy (IORT), the delivery of a single, large dose of irradiation at the time of surgery, was developed in order to administer higher doses of irradiation while displacing or shielding adjacent normal tissue structures from radiation exposure . 10 In pancreatic cancer, IORT has been offered for unresectable tumors to provide local tumor control and palliation of pain, [11][12][13][14][15][16] and for resectable tumors in an effort to improve local control and survival after PD. [11][12][13][14][15][16][17][18][19] Although a definitive survival benefit has not been observed, improvement of local control by IORT at the time of PD for resectable pancreatic cancer is supported by retrospective data, as well as by a prospective, randomized trial conducted at the National Cancer Institute (NCI).…”
Section: Discussionmentioning
confidence: 99%
“…10 In pancreatic cancer, IORT has been offered for unresectable tumors to provide local tumor control and palliation of pain, [11][12][13][14][15][16] and for resectable tumors in an effort to improve local control and survival after PD. [11][12][13][14][15][16][17][18][19] Although a definitive survival benefit has not been observed, improvement of local control by IORT at the time of PD for resectable pancreatic cancer is supported by retrospective data, as well as by a prospective, randomized trial conducted at the National Cancer Institute (NCI). [19][20][21] At our institution, IORT has been offered since 1986 in a dedicated operating suite located in the radiotherapy department for patients with either resectable or unresectable pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation